Designing a conceptual model for dynamic empowerment of medical science education managers - Mehdi Bagheri; Shahram Shayan; Fariba Jowkar (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Educational managers at universities of medical sciences are the suppliers of human resources to the healthcare system. Thus, attention to their professional empowerment can play a prominent role in improving the quality of medical science education. MATERIALS AND METHODS: The present study was implemented through the method of modeling and in the three stages of conceptual, modeling, and validation. The research environment was the medical science universities of Iran and the sampling method was purposive. The two qualitative approaches of literature review and semi-structured interview were used to develop the components of the model. The results were then integrated, the relationships between the components were investigated, and the model was eventually finalized. The resulting scores were analyzed using MicMac software. RESULTS: Twelve categories and 20 subcategories were identified in the first micro-study (desk research). Qualitative analysis of the interviews in the second stage led to the identification of 21 subcategories and seven categories. Components of the conceptual model were extracted from the results of the two first stages, both of which were aimed at the extraction of concepts relevant to dynamic empowerment of medical science educational managers, and the conceptual model for dynamic empowerment of medical science education managers was designed in the six categories of education, decision-making, organization, belief, dynamic capabilities, and environment after the interactions between the components were studied. CONCLUSIONS: Results of the present study revealed that dynamic empowerment of the managers is a multifaceted and multidimensional concept, and all of the factors incorporated in the conceptual model for dynamic empowerment of managers must receive special attention.